Model of Decision Making Behavior in Using Digital Banking Services: An Approach to Developing a Conceptual Framework that - Liau, Jennifer; Liberty, Evelyn; Faustine, Carine; Panggabean, Priska Basariana (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research aims to understand the decision-making behavior of a bank's customers in using digital banking services through the Decision-Making Behavior Model approach. By utilizing data collection methods through literature studies, as well as data processing methods through editing, classification, verification and conclusions, the analysis results show that technological advances have had a significant impact on consumer behavior in choosing banking services. The use of digital banking services has changed the way consumers interact with financial services, with an increasing preference for services that are convenient and easy to use. Implementing the Decision-Making Behavior Model allows banks to better understand customers' decision-making processes and identify specific actions to improve the user experience of digital banking services.